(untitled) (Bangladesh Journal of Zoology, 2017)
Fish species, fishing gear and crafts in the most polluted river Buriganga were inventorial. During December, 2012 to November, 2013, a total of 56 fish species belonging to 20 families and 9 orders were recorded. Cypriniformes observed to be the most dominant order with 18 species (32%). The highest fish diversity was recorded during monsoon season, and lowest during winter. Maximum diversity variance (7.616 ± 2.76 Sd) observed in the monsoon season for 56 species (220 individuals). Also 12 different types of gears of two categories (active and passive) and two types of crafts were observed to be used for fishing in the study area. The highest number of species of fishes (n = 56) recorded in August and lowest (n = 3) in April and May 2013. Strong correlation between water depth and number of fish species (r = 0.74) and fishing activities (r = 0.96) was observed. Bangladesh J. Zool. 45(1): 11-26, 2017